Criminological Review of Handling Hate Speech Issues (Case Study of West Jakarta Police Resort) (International Journal of Psychosocial Rehabilitation, 2020)
Hate speech is closely related to social media users who tend to want to get a sensation so that the posts they share become viral, although the posts are not necessarily true but many other social media users are spreading the news because they believe that the post is true. Hate speech itself is a crime against the honor of others because it is related to the good name of the person concerned or the organization or government whose reputation is tainted due to the posting of irresponsible people. The purpose of this study is to examine the legal provisions regarding hate speech, how the legal policy towards the perpetrators of hate speech crime, as well as how the efforts made by the police in tackling hate speech crime. The research conducted is empirical legal research supported by primary data by conducting interviews at the West Jakarta District Police and secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the study it is understood that the provisions regarding hate speech have been regulated in Indonesia not only in the Criminal Law Act alone, hate speech has even been regulated in a specific Law namely Law Number 11 of 2008 concerning Information and electronic transactions, only there are still many parties who ignore the law, so the police must make efforts to overcome it, the prevention efforts by the police should be further increased so that the utterance of hatred completely disappears from this beloved country because so many parties are harmed due to the crime . With the increase in legal efforts and in compliance with existing legal policies, many parties will feel justice and legal certainty so that there is no longer any fear of violence that has spread on social media so far, and it should be in this rapid development of the times that there should be greater self-awareness between individuals or groups to always appreciate the achievements made by other individuals or groups so that there is mutual respect in order to avoid the hate speech crime that has troubled many people.